2016
DOI: 10.1088/1475-7516/2016/04/030
|View full text |Cite
|
Sign up to set email alerts
|

Galactic dark matter search via phenomenological astrophysics modeling

Abstract: Abstract. Previous searches for the γ-ray signatures of annihilating galactic dark matter used predefined spatial templates to describe the background of γ-ray emission from astrophysical processes like cosmic ray interactions. In this work, we aim to establish an alternative approach, in which the astrophysical components are identified solely by their spectral and morphological properties. To this end, we adopt the recent reconstruction of the diffuse γ-ray sky from Fermi data by the D 3 PO algorithm and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 112 publications
3
46
0
Order By: Relevance
“…Here we make some simplifying assumptions to get a rough sense of the consistency between the observed signal and a possible DM interpretation. In particular, we check for consistency with the DM interpretation of the excess γ-ray emission observed in the Galactic center ( Huang et al 2013;Abazajian et al 2014;Zhou et al 2015;Calore et al 2015b;Abazajian et al 2015;Calore et al 2015a;Huang et al 2016;Ajello et al 2016;Daylan et al 2016;Carlson et al 2016;Ajello et al 2017;Karwin et al 2017;Ackermann et al 2017b;Agrawal & Randall 2017). This by no means encompasses all possibilities, and more detailed evaluations are left for future studies.…”
Section: The Smooth Component Of the Residual Emission In Fm31 And Damentioning
confidence: 98%
“…Here we make some simplifying assumptions to get a rough sense of the consistency between the observed signal and a possible DM interpretation. In particular, we check for consistency with the DM interpretation of the excess γ-ray emission observed in the Galactic center ( Huang et al 2013;Abazajian et al 2014;Zhou et al 2015;Calore et al 2015b;Abazajian et al 2015;Calore et al 2015a;Huang et al 2016;Ajello et al 2016;Daylan et al 2016;Carlson et al 2016;Ajello et al 2017;Karwin et al 2017;Ackermann et al 2017b;Agrawal & Randall 2017). This by no means encompasses all possibilities, and more detailed evaluations are left for future studies.…”
Section: The Smooth Component Of the Residual Emission In Fm31 And Damentioning
confidence: 98%
“…Decomposition into spectral components was used previously by several groups to determine the morphology of the excess, in particular, de Boer et al (2016) found that the excess emission resembles the distribution of molecular clouds near the GC, while Huang et al (2016) argued that the excess morphology is spherical. Motivated by the possibility that the excess comes from a population of MSPs (Brandt & Kocsis 2015), we add the third spectral component with an average spectrum of observed MSPs ∝ E −1.6 e −E/4 GeV (e.g., Cholis et al 2014;McCann 2015).…”
Section: Galactic Center Excess Template Derivationmentioning
confidence: 99%
“…Some studies claim that the excess appears to have a spherical morphology centered at the GC and spectral characteristics consistent with DM annihilation (e.g., Daylan et al 2016;Huang et al 2016), while de Boer et al (2016) find that the GC excess is correlated with the distribution of molecular clouds. Yang & Aharonian (2016) and Macias et al (2016) have argued that the morphology of the excess has a bi-lobed structure, which is expected for a continuation of the Fermi bubbles.…”
mentioning
confidence: 99%
“…Errors arise from the assumptions used to derive the model and may potentially have a large effect on the characterization of the different gamma-ray sources in Fermi data (Abazajian et al 2014). The Galactic diffuse background is the dominant component and confusion source within the ROI (Zhou et al 2015;Huang, Enßlin, & Selig 2016). Moreover, modeling of the bremsstrahlung emission of highenergy electrons interacting with the molecular gas contributes additional uncertainty.…”
Section: The Predicted Gamma-ray Fluxmentioning
confidence: 99%